2017
DOI: 10.1021/acsmacrolett.7b00097
|View full text |Cite
|
Sign up to set email alerts
|

P3HT-Based Photovoltaic Cells with a High Voc of 1.22 V by Using a Benzotriazole-Containing Nonfullerene Acceptor End-Capped with Thiazolidine-2,4-dione

Abstract: A novel A 2 −A 1 −D−A 1 −A 2 -type nonfullerene acceptor, using thiazolidine-2,4-dione (TD) as the terminal acceptor (A 2 ) for the first time, was designed and synthesized. The final molecule, BTA2, shows a high-lying lowest unoccupied molecular orbital (LUMO) of −3.38 eV and a wide optical band gap of 2.00 eV. Fullerene-free organic solar cells based on P3HT:BTA2 realized a high open-circuit voltage (V oc ) of 1.22 V with a power conversion efficiency (PCE) of 4.50%. These values are significantly higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
84
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 28 publications
0
84
0
1
Order By: Relevance
“…Many researches have proved that SMAs with twisted three-dimensional (3D) or quasi-3D structures are benefit to tune the blend morphology. [45,46] Therefore, SF and BTA are potential bulding blocks for constructing effective SMAs for OPV applications. [31][32][33][34][35][36] There are many electron-deficient units connected with the central SF unit to construct non-fullerene SMAs, such as benzothiadiazole (BT), [37,38] diketopyrrolopyrrole (DPP), [39][40][41] and perylene diimide (PDI).…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have proved that SMAs with twisted three-dimensional (3D) or quasi-3D structures are benefit to tune the blend morphology. [45,46] Therefore, SF and BTA are potential bulding blocks for constructing effective SMAs for OPV applications. [31][32][33][34][35][36] There are many electron-deficient units connected with the central SF unit to construct non-fullerene SMAs, such as benzothiadiazole (BT), [37,38] diketopyrrolopyrrole (DPP), [39][40][41] and perylene diimide (PDI).…”
Section: Introductionmentioning
confidence: 99%
“…We had devoted much efforts to develop a series of benzotriazole (BTA) based SMAs with A 2 ‐A 1 ‐D‐A 1 ‐A 2 skeleton, which provide a feasible model to investigate the effect of end‐capped group of A 2 . We found that the introduction of dicyanomethylene group into the terminal rhodanine segment could dramatically enhance the PCE when paired with different p‐type polymer .…”
Section: Introductionmentioning
confidence: 99%
“…The end groups have a significant effect on the lowest unoccupied molecular orbital (LUMO) levels and molecular packing behaviors. These nonfullerene acceptors were usually end‐capped with dicyanomethylene‐3‐indanone (IC), fluorinated IC, methylated IC, thienyl‐fused indanone, or rhodamine . Hou and co‐workers reported the acceptor ITCC, with thienyl‐fused indanone as end groups .…”
Section: Introductionmentioning
confidence: 99%
“…The side chains, which have included hexylphenyl, hexylthienyl, hexylselenophenyl, and alkyl groups, are also essential components of nonfullerene acceptors, which guarantee solubility, modulate aggregation behaviors, and adjust energy levels. π‐Bridges, such as benzothiazole, thiophene, diketopyrrolopyrrole, thiazole, were usually incorporated to elongate the π‐conjugation. Since these nonfullerene acceptors have excellent flexibility of structure modification and great potential to achieve high efficiency, there is much scope to investigations to optimize their chemical structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation